Life cycle environmental impacts of regeneration options for anion exchange resin remediation of PFAS impacted water. (1st December 2021) - Boyer, Treavor H.; Ellis, Anderson; Fang, Yida; Schaefer, Charles E.; Higgins, Christopher P.; Strathmann, Timothy J.
Highlights: Life cycle assessment showed trade-offs in environmental impacts for ion exchange. Impacts of disposal of waste regeneration solution dominated by incineration. Impacts were sensitive to amount incinerated and incineration waste type. Recycling the solvent or brine fraction of regeneration solution decreased impacts. Alternative salts for regeneration had lower impacts than incineration. Abstract: Although anion exchange resin (AER) treatment is considered an effective technology for removing per- and polyfluoroalkyl substances (PFASs) from impacted water, the environmental impacts associated with AER regeneration have not been systematically explored. In particular, the trade-offs of altering the composition of the regeneration solution and disposing of or recycling the waste regeneration solution are not known. To fill these important gaps in the literature, this research conducted a comparative life cycle assessment (LCA) of an AER-based PFAS remediation system with different regeneration scenarios including disposing of waste regeneration solution via incineration, reusing the organic cosolvent and brine fractions of the waste regeneration solution, and altering the composition of the regeneration solution to avoid organic cosolvent or NaCl. The results show that disposing of waste regeneration solution via incineration, without recycling organic cosolvent or brine, had the greatest environmental impact, and that incineration accounted for the greatest impact among contributing processes. Recycling of the cosolvent (or cosolvent and brine) fraction of the waste regeneration solution resulted in lower environmental impacts due to reduced mass of waste disposed of via incineration. Replacing NaCl in the brine with an alternative salt resulted in higher environmental impacts, with salts derived from chemical production, such as ammonium chloride and potassium carbonate, showing the largest increases in impacts. The results of this research highlight the importance of understanding the fate of PFASs during incineration, and the need for PFAS destruction technologies that can be coupled to AER regeneration to avoid incineration. Graphical abstract: Image, graphical abstract